PERAN SOSIALISASI DALAM MENCEGAH KEJAHATAN DIGITAL MASYARAKAT MODERN - Chirsna Nobert; Fajar Rizki Adhadi; Heru Narmuji; Ilham Saputra; Muhammad Ababil; Muhammad Gilang Sulaiman; Natio M.P; Rafly Dipoe Avianto; Rizky Putra Maulana; Sandi Nawawi (Abdi Jurnal Publikasi, 2024)
Digital crime, or cybercrime, is an increasingly prevalent threat in today’s digital era. This type of crime not only poses a risk to individuals but also damages the reputation of organizations and even nations. In this context, socialization plays a crucial role in raising public awareness about the dangers of digital crime and methods for prevention. This study aims to analyze how effective socialization can reduce the risks of digital crime within modern society. Through various educational approaches, such as seminars, digital campaigns, and the use of social media, the public is expected to recognize the signs of digital crime and protect themselves from these threats. The findings of this research indicate that the level of public understanding of digital crime increases with the intensity of socialization efforts. Therefore, continuous socialization involving various elements of society is key to preventing digital crime.